Characterization of Path-Loss Disparity in Virtual Multiple-Input-Single-Output Links - Haejoon Jung; Mary Ann Weitnauer (International Journal of Antennas and Propagation)
Cooperative transmission (CT) is an effective technique to achieve spatial diversity in fading environments, where spatially separated wireless nodes collaborate to form a virtual antenna array or virtual multiple-input-multiple-output (VMISO) link. Many authors model the path loss of the VMISO link as though the elements in the virtual antenna array are colocated, even though they are spread out. In this paper, we show that the spreading causes a signal-to-noise-ratio (SNR) penalty of up to 3 dB. Moreover, in the high SNR regime, we show that the performance degradation caused by the path-loss disparity can be characterized equivalently by log-normal distribution. We use these two observations to propose a new CT link model, expressed in closed form as an outage probability based on the log-normal shadowing model. The quality of the model is evaluated by a statistical test based on Kolmogorov-Smirnov method.